The American Jewish Experience and the Emergence of the Muslim Community in America (American Journal of Islam and Society, 1992)
Efforts to foretell the future of the American Jewish community date farback to the nineteenth century, and for the most part the prophecies have beenexceedingly gloomy. Former president John Adams predicted in a letter toModecai Noah in 1819 that Jews might "possibly in time become liberalUnitatian Christians.” A young American Jewish student named WilliamRosenblatt, writing in 1872, declared that the grandchildren of Jewish immigrantsto America would almost surely intermarry and abandon the rite of circumcision.Within fifty years “at the latest,” he predicted, Jews would be“undistinguishable from the mass of humanity which surrounds them.“ Justunder a century later, in 1964, Look magazine devoted a whole issue to the“Vanishing American Jew,” at the time a much-discussed subject. More recently,in 1984, Rabbi Reuven Bulka, in a book entitled The Orthodox-Reform Rift and the Future of the Jewish People, warned that “we are headingtowards a disaster of massive proportions which the North American Jewishcommunity simply cannot afford.”So far, thank God, all of these predictions have proven wrong. TheJewish people lives on. Some might consider this a timely reminder that (assomeone once said) “prediction is very difficult, especially about the future.“Othem may view our continuing survival as nothing less than providential:evidence that God, in a display of His divine mercy, is watching over us. Athird view, my own, is that precisely because Jews are so worried about survival,we listen attentively to prophets of doom and respond to them ...